The Effect of the Idiopathic Epiretinal Membrane and Surgically Induced Posterior Vitreous Detachment on the Retinal Nerve Fiber Layer - A. Altun (Journal of Ophthalmology)
Aim. To investigate the changes in the retinal nerve fiber layer (RNFL) following pars plana vitrectomy (PPV) with surgically induced posterior vitreous detachment (PVD) and idiopathic epiretinal membrane (ERM) and internal limiting membrane (ILM) peeling. Methods. Patients with unilateral ERM with vitreomacular traction were included in this prospective, randomized, and controlled clinical trial. The control group (Group 1) was formed with the nonoperated fellow eyes of the patients, and the study group (Group 2) was formed with the eyes that underwent PPV including idiopathic ERM and ILM peeling. In the preoperative and postoperative periods (1st, 2nd, 3rd, 6th, and 12th months), complete ophthalmological examination of the eyes was performed and RNFL measurements were examined in 4 different quadrants (superior, temporal, inferior, and nasal) with the help of spectral domain optical coherence tomography (OCT). Results. There was no statistically significant change in Group 1 during the follow-up period in all quadrants (p>0.05). The mean RNFL thickness in Group 2 was statistically significantly higher than in Group 1 in superior, inferior, and temporal quadrants (p<0.01), preoperatively. The mean RNFL in Group 2 was higher in the 1st, 2nd, 3rd, and 6th months and lower in the 12th month in superior, inferior, and temporal quadrants (p<0.01) when compared to the preoperative period. The mean RNFL thickness in the nasal quadrant in Group 2 was higher in the 1st, 2nd, and 3rd (p<0.01) months, same in the 6th month (p>0.05), and lower in the 12th (p<0.01) month when compared to the preoperative period. Conclusion. Idiopathic ERM may cause an increase in RNFL thickness in superior, inferior, and temporal quadrants with possible tractional effect. PPV with PVD induction and ERM and ILM peeling may cause these RNFL changes.